Influence of advancing age on clinical presentation, treatment efficacy and safety, and long-term outcome of pre-excitation syndromes: a retrospective cohort study of 961 patients included over a 25-year period. Issue 5 (17th May 2016) - Brembilla-Perrot, Béatrice; Olivier, Arnaud; Sellal, Jean-Marc; Manenti, Vladimir; Brembilla, Alice; Villemin, Thibaut; Admant, Philippe; Beurrier, Daniel; Bozec, Erwan; Girerd, Nicolas
Abstract : Objectives: There are very little data on pre-excitation syndrome (PS) in the elderly. We investigated the influence of advancing age on clinical presentation, treatment and long-term outcome of PS. Setting: Single-centre retrospective study of patient files. Participants: In all, 961 patients (72 patients ≥60 years (mean 68.5±6), 889 patients <60 years (mean 30.5±14)) referred for overt pre-excitation and indication for electrophysiological study (EPS) were followed for 5.3±5 years. Usual care included 24 h Holter monitoring, echocardiography and EPS. Patients underwent accessory pathway (AP) ablation if necessary. Primary and secondary outcome measures: Occurrence of atrial fibrillation (AF) or procedure-induced adverse event. Results: Electrophysiological data and recourse to AP ablation (43% vs 48.5%, p=0.375) did not significantly differ between the groups. Older patients more often had symptomatic forms (81% vs 63%, p=0.003), history of spontaneous AF (8% vs 3%, p=0.01) or adverse presentation (poorly tolerated arrhythmias: 18% vs 7%, p=0.0009). In multivariable analysis, patients ≥60 years had a significantly higher risk of history of AF (OR=4.2, 2.1 to 8.3, p=0.001) and poorly tolerated arrhythmias (OR=3.8, 1.8 to 8.1, p=0.001). Age ≥60 years was associated with an increased major AP ablation complication risk (10% vs 1.9%, p=0.006). During follow-up, occurrence of AF (13.9% vs 3.6%, p<0.001) and incidence of poorly tolerated tachycardia (4.2% vs 0.6%, p=0.001) were more frequent in patients ≥60 years, although frequency of ablation failure or recurrence was similar (20% vs 15.5%, p=0.52). In multivariable analysis, patients ≥60 years had a significantly higher risk of AF (OR=2.9, 1.2 to 6.8, p≤0.01). Conclusions: In this retrospective monocentre study, patients ≥60 years referred for PS work up appeared at higher risk of AF and adverse presentation, both prior and after the work up. These results suggest that, in elderly patients, the decision for EPS and AP ablation should be discussed in light of their suspected higher risk of events and ablation complications. However, these findings should be further validated in future prospective multicentre studies.